1999
DOI: 10.1128/iai.67.6.2841-2846.1999
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Osteoblastic Cell Differentiation by Lipopolysaccharide Extract fromPorphyromonas gingivalis

Abstract: Lipopolysaccharide from Porphyromonas gingivalis(P-LPS), an important pathogenic bacterium, is closely associated with inflammatory destruction of periodontal tissues. P-LPS induces the release of cytokines and local factors from inflammatory cells, stimulates osteoclastic-cell differentiation, and causes alveolar bone resorption. However, the effect of P-LPS on osteoblastic-cell differentiation remains unclear. In this study, we investigated the effect of P-LPS extract prepared by the hot-phenol–water method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
68
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 56 publications
11
68
0
5
Order By: Relevance
“…It is widely accepted that bacterial infections are responsible for alveolar bone destruction in periodontal disease (Nair et al 1996). Porphyromonas gingivalis LPS also significantly reduces osteoblast differentiation by inhibiting ALP, OC and osteopontin expression (Kadono et al 1999). Although E. faecalis is frequently isolated in root filled teeth with persistent periapical bone lesions, the effects of E. faecalis on osteogenesis and their underlying mechanisms are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that bacterial infections are responsible for alveolar bone destruction in periodontal disease (Nair et al 1996). Porphyromonas gingivalis LPS also significantly reduces osteoblast differentiation by inhibiting ALP, OC and osteopontin expression (Kadono et al 1999). Although E. faecalis is frequently isolated in root filled teeth with persistent periapical bone lesions, the effects of E. faecalis on osteogenesis and their underlying mechanisms are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In periodontitis, periodontal tissues are continuously challenged by periodontopathogens, such as P. gingivalis. It was shown that P. gingivalis could mediate the destruction of periodontal tissue and could be involved in alveolar bone resorption in various ways (40)(41)(42)(43)(44). In addition, the products of P. gingivalis were reported to have the ability to induce and activate host MMPs (19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…121,122 However, since OPN is produced by both osteoblasts and osteoclasts, it holds a dual function in bone maturation and mineralization as well as bone resorption. [123][124][125][126][127] Kido et al investigated the presence of OPN in GCF and the correlation between these levels and probing depth measures of periodontally healthy and diseased patients. Results from this study revealed that OPN could be detected in GCF, and increased OPN levels coincided with increased probing depth measures.…”
Section: Osteopontin (Opn)mentioning
confidence: 99%